2007
DOI: 10.1017/s0033291707000517
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and behavioural disinhibition in adult ADHD compared to borderline personality disorder

Abstract: Impaired inhibition is a core feature in adults with ADHD. In addition, slow RTs and high intra-individual variance in performance may reflect deficits in the regulation of activation and effort in ADHD patients. ADHD and BPD share some symptoms of behavioural dysregulation without common cognitive deficits, at least in the attentional realm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
98
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 49 publications
16
98
0
7
Order By: Relevance
“…This is is in line with previous studies that showed a tendency toward higher error rates in motor impulsiveness in patients with BPD than controls, although this difference was not significant. 19,42 Other studies have found significant group differences in go/no-go tasks between patients with BPD and healthy control participants. 17,18 It should be noted that for the present study we chose a relatively simple go/no-go task since brain activation during successful motor inhibition was the aim of our investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is is in line with previous studies that showed a tendency toward higher error rates in motor impulsiveness in patients with BPD than controls, although this difference was not significant. 19,42 Other studies have found significant group differences in go/no-go tasks between patients with BPD and healthy control participants. 17,18 It should be noted that for the present study we chose a relatively simple go/no-go task since brain activation during successful motor inhibition was the aim of our investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have reported performance deficits in go/no-go tasks, 17,18 while most others did not show impairments in patients with BPD. 16,19,20 Recent behavioural studies suggest that general deficits of BPD regarding impulsive behaviours may occur more on the motivational level in domains such as decision-making and delay of gratification. [20][21][22] Clinically, emotion dysregulation and impulsivity are closely linked in BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies did not find a different performance in go/no go tasks in groups of 9 patients each [11,20] . Similarly, other studies did not find differences between 24 BPD patients as compared to patients with major depression (MDD) and to HC in a stop signal task, a continuous performance task and a card sorting test [21] , or did not report significant differences between BPD subjects and HC in a stop signal task [22] . And while Nigg et al [23] found a significant correlation of r = 0.15 between BPD symptoms and the reaction time in a stop signal test even after controlling for other psychiatric disorders, intelligence was also correlated to BPD symptoms in this sample, which might explain the results as well.…”
Section: Empirical Findings On Impulsivity In Bpdmentioning
confidence: 98%
“…First, we hypothesized that, based on previous findings in selfreported impulsivity, anger, and aggression in BPD and ADHD, we would find higher scores on impulsivity in both patient groups compared with HCs. Second, we expected higher anger and aggression ratings and higher motor impulsiveness in ADHD patients compared with BPD patients (Krause-Utz et al, 2013;Lampe et al, 2007).…”
Section: Introductionmentioning
confidence: 96%